A new freshwater fabriciid species (Sabellida, Fabriciidae) from the Uruguay River, Argentina, with some remarks on the relationships of Monroika Hartman, 1951, Manayunkia Bourne, 1884 and Brandtika Jones, 1974 - Bick, Andreas; Armendáriz, Laura (Zootaxa, 2021)
Between the years 2007 and 2009 a hitherto unknown fabriciid species was found in the Lower Uruguay River, Argentina. Initially, it was assumed that this species could represent Manayunkia speciosa, a freshwater species originally described from North America. However, re-examinations have revealed that these specimens are clearly different from M. speciosa but they resemble Monroika africana. However, differences were also found that clearly distinguish this South American species from the African species so that it is described here as M. clarae sp. nov. The characters found in Monroika clarae sp. nov. make it also possible to compare and discuss these characters with those from the West African species Monroika africana, the Southeast Asian species Brandtika asiatica as well as Manayunkia species in terms of their systematic position. This mainly concerns the structure of the radiolar crown, the number of abdominal chaetigers, the presence of transitional chaetae as well as the structure of the thoracic and abdominal uncini. Potential origins of the freshwater Fabriciidae are also discussed.